Nutrition and ovarian activity in bovines: a review - Ferreira, Ademir de Moraes (Pesquisa Agropecuaria Brasileira, 1993)
It is well known that the reproductive performance is affected by the nutritional level, specially in terms of the onset of puberty, beginning of post-partum ovarian activity and on the maintenance of the oestrus cycle. Literature shows also results about the correlation between body weight changes and fertility (hormonal profile throughout the oestrus cycle, ovarian activity and conception rate). These inconsistent results may be due to the length of the feed restriction, body condition, age and physiological status of the animals (pregnant, lactating...). Underfeeding conditions may affect the reproduction system through several ways, directly or indirectly. This review shows the results of several research works dealing with the effects of the nutrition on reproduction, and how the effects are expressed.